2021
DOI: 10.1111/tri.13845
|View full text |Cite
|
Sign up to set email alerts
|

Recipient age and outcome after pancreas transplantation: a retrospective dual‐center analysis

Abstract: With a later onset of diabetes complications and thus increasing age of transplant candidates, many centers have extended upper age limits for pancreas transplantation. This study investigates the effect of recipient and donor age on outcomes after pancreas transplantation.We retrospectively analyzed 565 pancreas transplants performed at two Eurotransplant centers. The cohort was split at a recipient and donor age of 50 and 40 years, respectively. Median recipient age in old patients (≥50 years; 27.2%) was 54 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In 2021, Messner, et al reported on 124 SPKTs performed in patients ≥50 years of age at two Eurotransplant centers. 57 Although older patients had inferior patient survival compared to younger (<age 50, n = 367) SPKT recipients, they experienced less rejection, had similar relative risks for postoperative complications, and had comparable death-censored kidney and pancreas graft survival rates. Ten-year patient, kidney, and pancreas graft survival rates in the older group were 65.6%, 61.5%, and 44.8%, respectively.…”
Section: Afaneh Et Al Reported On 136 Consecutive Pancreas Transplants 17mentioning
confidence: 90%
See 1 more Smart Citation
“…In 2021, Messner, et al reported on 124 SPKTs performed in patients ≥50 years of age at two Eurotransplant centers. 57 Although older patients had inferior patient survival compared to younger (<age 50, n = 367) SPKT recipients, they experienced less rejection, had similar relative risks for postoperative complications, and had comparable death-censored kidney and pancreas graft survival rates. Ten-year patient, kidney, and pancreas graft survival rates in the older group were 65.6%, 61.5%, and 44.8%, respectively.…”
Section: Afaneh Et Al Reported On 136 Consecutive Pancreas Transplants 17mentioning
confidence: 90%
“…As a result, there has been an increase in SPKT in older patients that has appeared to have leveled off in the past five years. While outcomes in this population are mixed, [10][11][12][13][14][15][16][17][18][19][20][21][55][56][57][58][65][66][67] SPKT is generally supported when disease severity, comorbidity, and likely benefit are considered, rather than age alone. Limitations in the current data include the small number of patients represented in single-center retrospective analyses and the lack of granular information in registry data.…”
Section: Afaneh Et Al Reported On 136 Consecutive Pancreas Transplants 17mentioning
confidence: 99%
“…Small retrospective studies compared the outcomes of SPKT in younger recipients versus those >50; some reported worse graft outcomes in older recipients, whereas the majority, especially more recent ones, reported similar graft outcomes. 13-20…”
Section: Introductionmentioning
confidence: 99%
“…Small retrospective studies compared the outcomes of SPKT in younger recipients versus those >50; some reported worse graft outcomes in older recipients, whereas the majority, especially more recent ones, reported similar graft outcomes. [13][14][15][16][17][18][19][20] Background. The objective of this study was to compare the long-term outcomes of older (50-65 y) type 1 diabetics with body mass index <35 kg/m 2 and type 2 diabetics with body mass index <30 kg/m 2 who received simultaneous pancreas kidney transplantation (SPKT) versus living donor kidney transplants (LDKTs).…”
Section: Introductionmentioning
confidence: 99%